Prognostic factors influencing prolonged ventilation after open mitral valve surgery - Supomo Supomo (Faculty of Medicine, Universitas Andalas, 2020)
Objective: To determine prognostic factors influencing prolonged ventilation after surgery in our hospital. Method: Seventy-five patients fulfilled inclusion criteria were included in this retrospective cross-sectional study. Prognostic factors analyzed were age, chronic pulmonary disease, heart failure (NYHA class function), left ventricular (LV) dysfunction (based on ejection fraction), recent myocardial infarction, pulmonary hypertension (PH), duration of cardiopulmonary bypass (CPB), ischemic time and aorta clamp time, which were analyzed in relation to prolonged ventilation after open mitral valve surgery. Results: Subjects were 75 patients aged between 19 and 62 years old (mean 39.76, SD 11.44) whom underwent open mitral valve repair or replacement surgery. Twenty-three patients (30.67%) had prolonged ventilation (≥24 hours) after surgery. Bivariate analysis showed there were no significant correlation between age, heart failure, PH and LV dysfunction. There are different with statistically significance between groups (p<0.05). Conclusions: In this study, almost one-third of patients had prolonged ventilation after surgery. Factors influencing this morbidity were the duration of ischemic time, aorta clamp time and CPB. Age, heart failure, LV dysfunction and PH were not statistically related to the prolonged ventilation event.